Madurese Ethnic Congregation Jawi Wetan Christian Church Sumberpakem Village, Sumberjambe District, Jember Regency, 1945-2022 - Rizky Fajar Firmansyah; Sumarjono Sumarjono; Kayan Swastika; Akhmad Ryan Pratama; Mohamad Na’im; Gusti Ngurah Ary Kesuma Puja; Robit Nurul Jamil (History Education, University of Jember, 2023)
The existence of the Jawi Wetan Christian Church (GKJW) began with a number of people who claimed to believe in the Lord Jesus Christ as their savior and the first holy baptism on December 12, 1843 in Surabaya, East Java. Since that time their number increased and a fellowship of believers was formed, namely a fellowship of brothers in faith which then united themselves into one ecclesiastical fellowship on December 11, 1931. The formulation of the problem in this research were: 1) How was the development of the GKJW Madura Ethnic Congregation inSumberpakem village in 1945-2022 ?; 2) How was the religious life of the GKJW Madura Ethnic Congregation in Sumberpakem Village in 1945-2022? The results of the study show that the formation of the Madurese Christian Congregation originated from overseas or migration of Madurese living on Madura Island to East Java. The factor that drives them to migrate is the economic factor. At that time the condition of the land in the areas of Madura Island was barren so that their fields could not be planted so that they had difficulty meeting their daily needs. The organization of worship is a congregational assembly led by the local Pastor, another Pastor during service exchanges, or congregational assemblies taking turns according to the schedule. Worship at Greja Kristen Jawi Wetan Sumberpakem uses Madurese or Indonesian according to the schedule made by the relevant commission, namely the Theological Commission. Keywords: Church Congregation, Madurese Ethnicity, GKJW